Iron partitioning in the upper 300 m of the water column during the cruise ANT-XXVIII/3 in waters of the Southern Ocean - Luis Miguel Laglera; Juan Santos-Echeandía; Lisa Fischer; Stephan Hann (PANGAEA, 2025)
Iron concentrations in unfiltered and filtered seawater, using different pore sizes were determined in the upper 300 m of the water column during cruise ANT-XXVIII/3 in waters of the Southern Ocean. Iron concentrations were analysed onboard by voltammetry after at least 24 h acidification at pH 2.0 and addition of 2,3 dihydroxynaphtalene (Laglera et al., 2013). The cruise initially sampled a North-South transect across the Antarctic Polar Front (APF) at 10E.